Bathymetry, substrate and fishing areas of Southeast Atlantic high-seas seamounts. Issue 1 (2nd January 2019) - Bergstad, OA; Høines, ÅS; Sarralde, R; Campanis, G; Gil, M; Ramil, F; Maletzky, E; Mostarda, E; Singh, L; António, MA
Abstract : Most of the Southeast Atlantic Ocean is abyssal, and global bathymetries suggest that only ∼3.2% of the areas beyond national jurisdiction (ABNJ; also known as the high seas, as defined in the United Nations Convention on the Law of the Sea [UNCLOS]) are shallower than 2 500 m. This study mapped bathymetry and characterised substrates in selected seamount summit areas, including several that have been or may become fishing areas. The southernmost location, the Schmitt-Ott Seamount, has exposed volcanic bedrock with surrounding flats covered by thin biogenic sediments and/or coral rubble that appears ancient. At Wüst, Vema, Valdivia and Ewing seamounts the basaltic base appears to be overlain by coral caps and other coral substrates (sheets, rubble). Adjacent summit plains have biogenic sediments of varying thickness. Vema has a flat, roughly circular summit, <100 m deep, with the shallowest point being a 22-m-deep summit knoll; the upper slopes have ancient coral framework, but the summit has a mixture of coralline and volcanic rock and coarse sediments, including extensive areas with coralline algae and kelp forests. Valdivia Bank is a 230-m-deep, flat, rocky area (∼11 × 5 km), protruding steeply from the extensive multi-summit Valdivia subarea of the Walvis Ridge. The distribution of past fisheries in the Convention Area of the South East Atlantic Fisheries Organisation (SEAFO) was considered in relation to the new information on bathymetry and substrate.